1986
DOI: 10.1016/s0735-1097(86)80040-7
|View full text |Cite
|
Sign up to set email alerts
|

Patent ductus arteriosus in adults-long-term follow-up: Nonsurgical versus surgical treatment

Abstract: The long-term prognosis of adult patients with patent ductus arteriosus treated medically or surgically has not been demonstrated. One hundred seventeen adult patients ranging in age from 18 to 81 years (mean 36) were followed up for 1 to 37 years (mean 18). Forty-five patients were treated nonsurgically and 72 had surgical closure. The nonsurgical group experienced significantly more cyanosis (p = 0.002) and had fewer diastolic murmurs (p greater than 0.001) than did the surgical group. In the nonsurgical gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 11 publications
1
37
0
3
Order By: Relevance
“…(7) There is a higher incidence of PDA among preterm infants, and in most studies, the male to female ratio has been reported to be 1:2. (2) While PDA is usually diagnosed early in life, subclinical PDA is a rare entity in the adult and elderly population, (8,9) traditionally investigated and diagnosed only after the patient becomes symptomatic. (5) Occasionally, silent PDA may be discovered incidentally on MDCT performed for other purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(7) There is a higher incidence of PDA among preterm infants, and in most studies, the male to female ratio has been reported to be 1:2. (2) While PDA is usually diagnosed early in life, subclinical PDA is a rare entity in the adult and elderly population, (8,9) traditionally investigated and diagnosed only after the patient becomes symptomatic. (5) Occasionally, silent PDA may be discovered incidentally on MDCT performed for other purposes.…”
Section: Discussionmentioning
confidence: 99%
“…(4,6,10) Fisher et al suggested that some patients may tolerate very high pulmonary arterial pressure for long periods without deterioration of their clinical status. (9) However, unrepaired PDA in these asymptomatic patients may eventually become clinically significant, particularly in conjunction with an acquired physiological insult from recurrent pneumonia, development of chronic obstructive pulmonary disease, ischaemic heart disease or calcific aortic stenosis. (2,3) In addition, there is an associated risk of infective endarteritis, even in small PDAs, estimated to be up to 0.45% per year after the second decade of life.…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca tedavisiz bırakılan geniş PDA'larda pulmoner vasküler direncin geri dönüşümsüz yükselmesi sonucu Eisenmenger sendromu gelişebilir. [3] Orta ve geniş çaplı PDA'lar konjestif kalp yetersizliği semptomlarını kontrol etmek, uzun dönem kalp ve akciğer komplikasyonlarını önlemek için kapatılmalıdır. [1,4,5] Bu hastalarda yaşamın ikinci on yılında infektif endarterit gelişme riski konjestif kalp yetmezliği gelişme riskinden daha fazladır.…”
Section: Discussionunclassified
“…In adults, the anatomy of the PDA is significant for the presence of calcification in the area of the aortic isthmus and pulmonary artery may cause a problem for surgical closure. When a PDA occurs in isolation, device closure is usually feasible and can be successfully performed in the vast majority of adults with a very low complication rate (15,16). Surgical closure of a PDA in the adult is reserved for the patient with a duct too large for device closure or with inappropriate anatomy and cardiac operations are indicated due to other concomitant cardiac lesions (Table 3).…”
Section: Transcatheter Device Closure Of Patent Ductus Arteriosusmentioning
confidence: 99%